The contradictions involving guardianship in Brazilian Private Law and their possible solutions - Soares, Paula Santiago [UNESP]; Canela, Kelly Cristina [UNESP] (My University, 2023)
This research analyzes the legal framework of guardianship, mainly after the legislative changes established by the Brazilian Persons with Disabilities Act and the 2015 Code of Civil Procedure, which brought a series of contradictions related to the legal aspects of guardianship. In order to solve these antinomies, we shall use methods of interpretation involving the history, hierarchy and specificity of such norms, as well as the comparative, dialectical and deductive-bibliographic methods. The paper then concludes with a proposed solution to the conflict of rules involving guardianship as well as analyzing the Brazilian Senate Bill 757/2015, which may serve as a concrete solution for the problems mentioned herein.
A antinomia que cerca a curatela e suas possíveis soluções
Keywords: Antinomy; Brazilian Code of Civil Procedure; Guardianship. Persons with Disabilities Act; Legal capacity